A synthesis of evidence on inhibitory control and auditory hallucinations based on the Research Domain Criteria (RDoC) framework - Badcock, Johanna C.; Hugdahl, Kenneth (Frontiers in Human Neuroscience, 2014)
The National Institute of Mental Health initiative called the Research Domain Criteria (RDoC) project aims to provide a new approach to understanding mental illness grounded in the fundamental domains of human behaviour and psychological functioning. To this end the RDoC framework encourages researchers and clinicians to think outside the [diagnostic]box, by studying symptoms, behaviours or biomarkers that cut across traditional mental illness categories. In this article we examine and discuss how the RDoC framework can improve our understanding of psychopathology by zeroing in on hallucinations- now widely recognized as a symptom that occurs in a range of clinical and non-clinical groups. We focus on a single domain of functioning - namely cognitive [inhibitory] control - and assimilate key findings structured around the basic RDoC "units of analysis", which span the range from observable behaviour to molecular genetics. Our synthesis and critique of the literature provides a deeper understanding of the mechanisms involved in the emergence of auditory hallucinations, linked to the individual dynamics of inhibitory development before and after puberty; favours separate developmental trajectories for clinical and nonclinical hallucinations; yields new insights into co-occurring emotional and behavioural problems; and suggests some novel avenues for treatment.